2014
DOI: 10.1007/s00066-014-0686-1
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells are sensitive to treatment with kinase inhibitors and ionizing radiation

Abstract: These data show that MSCs are highly sensitive to RKIs and combination treatments incorporating IR. Expression analyses suggest that high levels of PDGF receptors may contribute to this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Several analyses have so far provided inconsistent results regarding the sensitivity of MSCs against various chemotherapeutic agents like etoposide, vincristine, cisplatin, kinase inhibitors or ionizing radiation192425262728. A relative in-vitro resistance of MSCs against vincristine, cisplatin or etoposide has been demonstrated in cell culture experiments, and bone marrow samples of patients treated with these drugs have been shown to harbor viable and proliferating MSCs, confirming the observed resistant phenotype in vivo 2930.…”
Section: Discussionmentioning
confidence: 99%
“…Several analyses have so far provided inconsistent results regarding the sensitivity of MSCs against various chemotherapeutic agents like etoposide, vincristine, cisplatin, kinase inhibitors or ionizing radiation192425262728. A relative in-vitro resistance of MSCs against vincristine, cisplatin or etoposide has been demonstrated in cell culture experiments, and bone marrow samples of patients treated with these drugs have been shown to harbor viable and proliferating MSCs, confirming the observed resistant phenotype in vivo 2930.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis compared the effects of photon and carbon ion irradiation on the survival and functional properties of human mesenchymal stem cells. While previous analyses have shown relative radioresistance of MSCs after photon irradiation, no data are available regarding other forms of radiation such as carbon particle radiotherapy despite their clinical use [ 12 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The radiation response of MSCs has been analyzed both in mouse and human cell samples; several studies using high-dose irradiation have demonstrated that the in-vitro survival of MSCs was considerably higher than that of other bone marrow-derived stem cells and was similar to other rather radio-resistant cell lines [ 64 - 66 ]. Another analysis demonstrated increased radiation resistance of adult human MSCs compared to embryonic stem cells [ 67 ].…”
Section: Influence Of Ionizing Radiation On Mscsmentioning
confidence: 99%